2023
DOI: 10.1037/ebs0000279
|View full text |Cite
|
Sign up to set email alerts
|

Does pathogen avoidance affect intergroup categorization? Replication of Makhanova, Miller, and Maner (2015).

Abstract: Because pathogens have posed persistent threats to people (and other species) throughout history, evolution has produced behavioral and psychological mechanisms aimed at avoiding pathogens. One mechanism may involve avoidance of others who possess heuristic cues to disease. Past research suggests that, when concerns about pathogens are salient, people tend to categorize such targets (e.g., elderly targets, racial outgroup members) as outgroup members. In light of the recent debate regarding links between patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Immigrant generation status has also been linked with analgesic prescribing practices; third-generation or greater Mexican Americans were 4 times more likely to be prescribed opioids to treat their chronic pain compared to first generation Mexican Americans (Hollingshead et al, 2022). It is worth nothing that pathogen avoidance can also contribute to bias against patients from other groups heuristically associated with disease such as people who are elderly (Duncan & Schaller, 2009;Makhanova et al, 2021) or overweight (Park et al, 2007;Lund & Miller, 2014;Makhanova et al, 2021;Miller & Maner, 2012). Future research should directly examine how pathogen avoidance may contribute to biased patient care decisions and health disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrant generation status has also been linked with analgesic prescribing practices; third-generation or greater Mexican Americans were 4 times more likely to be prescribed opioids to treat their chronic pain compared to first generation Mexican Americans (Hollingshead et al, 2022). It is worth nothing that pathogen avoidance can also contribute to bias against patients from other groups heuristically associated with disease such as people who are elderly (Duncan & Schaller, 2009;Makhanova et al, 2021) or overweight (Park et al, 2007;Lund & Miller, 2014;Makhanova et al, 2021;Miller & Maner, 2012). Future research should directly examine how pathogen avoidance may contribute to biased patient care decisions and health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…However, environmental conditions can also elevate pathogen disgust, such as in Polish women during the COVID-19 pandemic (Milkowska et al, 2021). Momentary increases in pathogen avoidance may also occur when people both see images of others who are ill or read articles about impending illness threats (Makhanova et al, 2021). Little is known, however, about how prolonged exposure to environmental stimuli that signal the presence of pathogens affects both pathogen avoidance and resulting bias.…”
Section: Introductionmentioning
confidence: 99%
“…Participants rated their feelings (0 = extremely cold, 100 = extremely warm) toward various groups of hypothetical patients (e.g., "patients who are obese," "patients who have not gotten the COVID-19 vaccine") using electronic sliders (i.e., feelings thermometers). For the second measure of bias, participants read a brief text passage about a fictional country in Central Africa named Krasnee (Faulkner et al, 2004;Makhanova et al, 2023) and rated their perceptions of Krasneeians as likable, trustworthy, open-minded, hostile, ignorant, poor, and unclean (1 = not at all, 7 = very much). Prior work using this measure has found that participants responding with a Xenophobic response to the Krasneeians tended to rate them lower on likable and trustworthy but higher on unclean (Faulkner et al, 2004;Makhanova et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…We also explored whether IMS scores would predict prejudice related responses regarding the fictional Krasneeans particularly for the traits likable, trustworthy, and unclean (Faulkner et al, 2004;Makhanova et al, 2023). IMS was a significant predictor for describing Krasneeans as likable, trustworthy, and less unclean, but not for hostile, open-minded, ignorant, nor poor.…”
Section: Internal Motivation To Respond Without Prejudice (Ims) and Biasmentioning
confidence: 99%